Linked : conquer LinkedIn. Land your dream job. Own your future. - Garriott, Omar; Schifeling, Jeremy (Workman Publishing, 2022)
"Here, from two LinkedIn experts and former employees, is the definitive guide that demystifies the massive site and gives every reader--from the newly minted college graduate to the midlife career-changer--the most important strategies to win the modern job search game. Clear, lively, and decidedly practical, Linked shows how to burnish your personal brand so recruiters come to you. Tap the power of the network effect and turn anyone into an invaluable referral. think like employers and focus your profile to get noticed, get considered, and get hired. And game both the search algorithm and the Applicant Tracking Systems used by nearly every employer in every economic sector. The result: not just a great job, but the future of your dreams."--Page 4 of cover.